The music of radiohead : creativity and optimism in a post-postmodern world - Saeful Hakim Aziz (Nanyang Technological University, 2017)
Radiohead, a rock band hailing from Oxford in England which to date has released nine full length albums, have over the years been revered in the music industry for their approach to music making. The band has mastered a creative, eclectic approach in their praxis of music making, which has seen them transgress the conventions of rock music as a genre, even challenging notions of the “song” at some points, while at the same time maintaining a mainstream appeal. Radiohead’s ethos of creativity and experimentation have established the band as the pre-eminent innovators of their generation, primarily in the context of rock music. To date, Radiohead has amassed as much as 22 awards from 79 nominations, which include 3 Grammy awards for Best Alternative Music Album.